AFFIRMATIVE ACTION DI ACEH: KENDALA DAN UPAYA PARTAI POLITIK DALAM MENINGKATKAN KETERWAKILAN PEREMPUAN - Novita Sari (Journal of Political Sphere, 2020)
This study aims to help us understand and examine the obstacles faced by political parties in conducting the political recruitment of women legislative candidates in Aceh and analyze the efforts made by political parties in order to increase women's participation and capacity in the political field. This study uses descriptive qualitative research methods that aim to provide information through data mining in order to produce a complete data description. This can be seen from the effectiveness of the implementation of affirmative action policies that have been running so far in increasing women's representation in parliament both at the national and local levels in Aceh. The implementation of affirmative action policies that must be fulfilled by political parties has become a separate challenge for political parties, where in the effort to meet the gender quota political parties have obstacles, including due to the patriarchal culture that is still growing in Acehnese society, human resources (women) who are still minimal, financial limitations of women, as well as regulation and a sense of comfort with what women have obtained. To answer these various obstacles, political parties have also made various efforts, such as providing intensive political education, placing female legislative candidates in small serial numbers, tightening the political recruitment process, and providing material and non-material support. The success of political parties in realizing the ideals of implementing affirmative action policies is greatly influenced by how the role of political parties can internally maintain the existence of parties with adequate and structured institutions.Keywords:Policies, affirmative action, women, political parties